Standing Rules of Order of the Cleveland City Council: With a Catalogue of the Mayors and Councils of the City of Cleveland, from Its Organization, April, 1836, to April, 1871, and Officers of the City Government for 1872, at 101, An Ordinance to Prevent the Firing of Guns and Fire-works, § 1 (1872) - (:unkn) unknown (My University, 1856)
That no person shall fire any cannon, gun, rifle, pistol, or fire-arms of any kind, or fire or explode any squib, rocket, cracker, Roman candle, or other combustible fire-works within the city.§
Keywords: DISCHARGE